Protection of the digital Holy Quran hash digest by using cryptography algorithms - Alahmad, Mohammad; Alshaikhli, Imad Fakhri Taha; Moh. Jumaah, Bashayer (2013)
With the rapid technological advances, possibility of tampering information have been increased. Cryptography is the science of information security that includes symmetric encryption and asymmetric encryption which used to avoid the tampering attempts and guarantee the data integrity. This paper discusses a cryptography algorithm (CARCA), which is combination between two types of cryptography (symmetric cryptography "AES" and asymmetric cryptography "RSA"). The objective of this paper demonstrating CARCA method to encrypt the outputted hash digest generated by Gear hash function for protecting the digital Holy Quran.